Cell size anomalies in the auditory thalamus of rats with hypoxic‐ischemic injury on postnatal day 3 or 7. Issue 33 (30th October 2013) - Alexander, Michelle; Garbus, Haley; Smith, Amanda L.; Fitch, R. Holly
Abstract: Children born prematurely (<37 weeks gestational age) or at very low birth weight (VLBW; <1500 g) are at increased risk for hypoxic ischemic (HI) brain injuries. Term infants can also suffer HI from birth complications. In both groups, blood/oxygen delivery to the brain is compromised, often resulting in brain damage and later cognitive delays (e.g., language deficits). Literature suggests that language delays in a variety of developmentally impaired populations (including specific language impairment (SLI), dyslexia, and early HI‐injury) may be associated with underlying deficits in rapid auditory processing (RAP; the ability to process and discriminate brief acoustic cues). Data supporting a relationship between RAP deficits and poor language outcomes is consistent with the "magnocellular theory, " which purports that damage to or loss of large (magnocellular) cells in thalamic nuclei could underlie disruptions in temporal processing of sensory input, possibly including auditory (medial geniculate nucleus; MGN) information This theory could be applied to neonatal HI populations that show subsequent RAP deficits. In animal models of neonatal HI, persistent RAP deficits are seen in postnatal (P)7 HI injured rats (who exhibit neuropathology comparable to term birth injury), but not in P1‐3 HI injured rodents (who exhibit neuropathology comparable to human pre‐term injury). The current study sought to investigate the mean cell size, cell number, and cumulative probability of cell size in the MGN of P3 HI and P7 HI injured male rats that had previously demonstrated behavioral RAP deficits. Pilot data from our lab (Alexander, 2011) previously revealed cell size abnormalities (a shift toward smaller cells) in P7 but not P1 HI injured animals when compared to shams. Our current finding support this result, with evidence of a significant shift to smaller cells in the experimental MGN of P7 HI but not P3 HI subjects. P7 HI animals also showed significantly fewer cells in the affected (right) MGN as compared P3 HI and shams animals. Moreover, cell number in the right hemisphere was found to correlate with gap detection (fewer cells = worse performance) in P7 HI injured subjects. These findings could be applied to clinical populations, providing an anatomic marker that may index potential long‐term language disabilities in HI injured infants and possibly other at‐risk populations.